Pancreatic ductal cells may have a negative effect on human islet transplantation. - Sandra Marín-Cañas; Elisabet Estil Les; Laura Llado; Patricia San José; Montserrat Nacher; Noèlia Téllez; Eduard Montanya (PLoS ONE, 2019)
Aim To evaluate the effect of pancreatic ductal cells on experimental human islet transplantation. Materials and methods Isolated islets were additionally purified by handpicking. Ductal cells were purified by magnetic cell sorting and then clustered into ductal pancreatospheres (DPS). Islets, DPS, and islets + DPS (100 islets + 75 DPS, or 100 islets + 200 DPS) were cultured and glucose-stimulated insulin secretion, β-cell apoptosis, and gene expression was determined. Islets and islets + DPS preparations (800 islets + 600 DPS) were transplanted to streptozotocin-treated immunodeficient mice and glycemia, graft morphometry, and gene expression were determined. Results Insulin stimulation index was higher in islets than in islets co-cultured with DPS (5.59 ± 0.93 vs 4.02 ± 0.46; p<0.05). IL1B and CXCL11 expression was higher in 100 islets + 200 DPS than in islets (p<0.01), and IL-1β was detected in supernatants collected from DPS and islets + DPS preparations, but not in islets. Hyperglycemia developed in 33% and 67% of mice transplanted with islets or with islets + DPS respectively. β-cell mass was 26% lower in islets + DPS than in islets grafts (p>0.05), and the ratio β-/endocrine non-β-cell mass was lower in islets + DPS grafts (islets: 2.05 ± 0.18, islets + DPS: 1.35 ± 0.15; p<0.01). IL1B and IL1RN expression was significantly higher in islets + DPS grafts. Conclusions Islet preparations enriched with ductal cells have a lower insulin stimulation index in vitro and achieved a worse metabolic outcome after transplantation. Inflammation may mediate the deleterious effects of ductal cells on islet cells.